PELATIHAN PEMBUATAN MASKER DAUN KELOR - Agus Afriliyanto (Karsa Bhakti : Journal of Community Service, 2026)
This Community Service activity aims to empower the people of Cabean Village, Cepu District, Blora Regency by utilizing the local potential of Moringa leaves as a basic ingredient for making natural face masks with economic value. So far, Moringa leaves have only been used for household consumption and have not been processed into beauty products that have a higher selling value. This assistance uses counseling and training for 25 participants with housewife backgrounds in Cabean village. The main target of this activity is housewives as an effort to increase skills and economic independence. The results of the activity show that the community is able to understand the benefits of Moringa leaves, practice the process of making masks independently, and produce Moringa leaf mask products that can be marketed. This product is attractively packaged and marketed at an affordable price of IDR 10,000 per package, and has received a positive response and high enthusiasm from the public. This activity has a positive impact in increasing knowledge, skills and opening up business opportunities based on the potential of local villages.